The importance of artisanal and small-scale mining for rural economies: Livelihood diversification, dependence, and heterogeneity in rural Guinea. (August 2022) - Huntington, Heather; Marple-Cantrell, Kate
Abstract: A number of development interventions have sought to improve livelihoods and benefits in diamond mining communities. Local interventions can include activities such as formalizing and securing the tenure of mining claims, converting mining sites to agricultural sites, alternative livelihoods, land use planning, and training miners in SMARTER mining techniques. However, there are strong assumptions underlying the program logic and context for many of these interventions. To interrogate these assumptions, this paper explores livelihood dependence and motivations for ASM, in-formality and rules, and environmental costs with a focus on differential responses for indigene miners versus national and transnational miners, as well as for full-time career miners versus part-time miners. We also analyze the variation in responses across two diamond mining areas. The findings challenge several key assumptions that inform development programming around alternative livelihoods and formalization in the context of ASM. The results demonstrate that ASM is fully embedded in the local economy in the study area, although there is significant heterogeneity in livelihood dependence and diversification within and between mining sites. We find that low conflict results challenge the general association of artisanal miners and violence, in part due to effective customary systems for land management. The analysis highlights elements of ASM management that would benefit from programs or policies that seek to facilitate ASM as a sustainable approach for local economic growth. Highlights: the embeddedness of ASM in rural economies and farming communities. Provides detailed information about livelihood diversification and mining dependence. Highlights low levels of conflict and effective customary systems for ASM management. Demonstrates significant geographic heterogeneity within and between mining sites. Identifies barriers to alternative livelihoods and formalization programs in rural settings.